Refining the definition and typologies of entrepreneurship in Africa: A systematic review - Wellington Chakuzira; John Michael Maxel Okoche; Marcia Mkansi (Administrative Sciences, 2024)
This paper aims to describe a highly pervasive and under-reported context-specific phenomenon of entrepreneurship, specifically in light of the rise in different types of entrepreneurial activities in Africa. Explicably, this paper accepts that entrepreneurship typologies are different across the globe. Utilising the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), a total of 1230 articles were discovered from Scopus, Web of Science, and ProQuest databases. Subsequently, a screening for suitability was conducted, resulting in the exclusion of 1200 articles based on criteria such as publication year, jurisdiction, and abstract review. Ultimately, 30 journal articles were imported into Zotero Reference Manager and Atlas for further examination. This study found that a state of entrepreneurship mishap exists in Africa. The utilisation of a uniform approach in supporting entrepreneurs is identified as another challenge. Lastly, this study introduces nine novel entrepreneur typologies: Lifepreneurs, Part-timers, Hobbypreneurs, Entremployees, Empreneurs, Techpreneurs, Carte-blanche, Profeneurs, and Smartpreneurs. These typologies serve as a conceptual framework for categorising various entrepreneurial initiatives based on a true reflection of the African entrepreneurial ecosystem, attributes, and key success factors. Theoretically, our paper fills a gap in the academic literature regarding the study of entrepreneurship in developing countries and its classifications. Practically, this paper could offer African policymakers a blueprint for supporting startups at a local level. Significantly, this work stands out for providing a classification system that captures the authentic nature of entrepreneurial undertakings within African economies.
Keywords: 350; entrepreneurial classification; entrepreneurial typologies; entrepreneurship; systematic review; typology matrix